2008
DOI: 10.1111/j.1475-2743.2008.00179.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of tillage intensity on soil structure and winter wheat root/shoot growth

Abstract: Despite a vast amount of data on the effect of tillage on crop productivity, surprisingly there is little detailed information available on the influence on below and aboveground crop growth dynamics. Such information is essential for developing sustainable cropping systems. The objective of this study was to investigate the effect of tillage intensity on crop growth dynamics and soil structure. A tillage experiment was established in autumn 2002 on two Danish sandy loams (Foulum and Flakkebjerg) in a cereal‐b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
43
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 38 publications
8
43
0
Order By: Relevance
“…In this study, we also observed significantly higher average soil bulk density in DD (1.46) relative to CT (1.42), which implies a higher penetration resistance in DD than in the CT plots. Similarly, Munkholm et al (2008) observed a higher root penetration resistance and low oxygen availability in DD relative to CT plots in our present a Relative distribution (%) between soil depths within specific pools; for each treatment column value followed by different letters are significantly different P<0.05; R = roots, S = soil trial. This implies that our DD plots are subject to soil compaction, root penetration resistance and low oxygen availability, which are important factors for root proliferation in the soil profile.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…In this study, we also observed significantly higher average soil bulk density in DD (1.46) relative to CT (1.42), which implies a higher penetration resistance in DD than in the CT plots. Similarly, Munkholm et al (2008) observed a higher root penetration resistance and low oxygen availability in DD relative to CT plots in our present a Relative distribution (%) between soil depths within specific pools; for each treatment column value followed by different letters are significantly different P<0.05; R = roots, S = soil trial. This implies that our DD plots are subject to soil compaction, root penetration resistance and low oxygen availability, which are important factors for root proliferation in the soil profile.…”
Section: Discussionmentioning
confidence: 63%
“…The main experiment was established in Autumn 2002 and has been subject of a number of earlier studies (Chatskikh and Olesen 2007;Munkholm et al 2008;Mutegi et al 2010). The experiment had a split-plot design with four replicate blocks, each with crop rotation as main treatment and tillage treatments in subplots .…”
Section: Experimental Designmentioning
confidence: 99%
See 2 more Smart Citations
“…The increase in Pc with depth without significant BD modification suggested an increased number of contact points per unit volume resulting from the agglomeration of fine particles under the long-term action of mechanical loads, climatic agents, biological organisms and/or clay minerals acting as cementing agents, especially in RT18 (Guérif, 1994). This process could be responsible for negative effects on root growth and root-induced parameters, leading to more superficial root lateral development sometimes observed in RT (Munkholm et al, 2008;Dal Ferro et al, 2014). In the topsoil in RT18, r max and PSD max were the lowest among the layers considered.…”
Section: Porosity Structurementioning
confidence: 99%